Recognition and behavioral assessment of acute pain in cats: literature review - Marco Aurélio Amador Pereira; Karina D'Angelo Campos; Marina Caetano Evangelista; Lucas Alaião Gonçalves; Rosana Souza Thurler; Júlio Ken Nagashima; Sérgio Grandisoli Garcia Filho; Clarissa Muniz Ribeiro; Denise Tabacchi Fantoni (Brazilian Journal of Veterinary Research and Animal Science, 2017)
Although pain is considered the 4th vital sign and one of the most frequently observed clinical signs in domestic animals’ clinical practice, its treatment is still inadequate despite significant improvement in the last few years. Acute post-operative pain has aroused great interest due to its potential risk of developing into chronic pain, and if not treated properly, it might worsen the recovery and the patient’s quality of life. Cats are one of the least studied species of domestic animals regarding pain recognition and control. Some of the difficulties lie in pain assessment and perception. The consensus published in February 2016 about behavioral signs of pain in cats considered some signs to be reliable and sensitive for the assessment of pain in this species in many different clinical conditions, however it still states that more studies will be necessary in order to evaluate its clinical validity and applicability, especially considering the various pain intensities. As an attempt to quantify pain intensity in cats, several types of traditional subjective scales and others that facilitate pain assessment by combining the observation of spontaneous behavioral signals of pain and qualitative response to palpation of surgical wound are used as tools. It is necessary to use specific scales for each type of pain and for each specific animal species so to minimize the subjectivity and the partiality of the observers, reducing bias and improving efficacy, thus leading to a better patient care.